L’architettura dei Luoghi Comuni: un dialogo con Carlana Mezzalira Pentimalli - Federica Serra (ArchAlp)
The issue of “Common Places” is explored in this contribution as a reflection on architecture’s ability to create generous spaces that serve human relationships, blending a sense of community with domesticity. Through an interview with Michel Carlana, co-founder of the Carlana Mezzalira Pentimalli studio, this essay examines examples that embody this feature of architecture, such as the School of Music and the Civic Library in Bressanone. Carlana illustrates how architecture can mediate between historical and contemporary elements, public and private realms, by emphasising the void as a social infrastructure and thresholds as dynamic meeting points. Central to this approach are shared design processes and attentive engagement with communities, fostering a transfer of responsibility from architect to inhabitants, who come to recognise and claim ownership of these spaces. The thoughtful selection of materials, grounded in context, enhances coherence and integration with the surrounding landscape and urban fabric. Ultimately, Carlana suggests that Alpine territories can serve as experimental grounds for philanthropic architectural practices, offering models that can be adapted to urban environments.